Challenging Coasts Transdisciplinary Excursions into Integrated Coastal Zone Development - Visser, Leontine E. (MARE Publication Series, 2004)
Following its launch at the Earth Summit in Rio de Janeiro in 1992, Integrated Coastal Zone Management (ICZM) became a key tool for national governments and international organisations alike. This volume argues that transdisciplinarity is a necessary corollary of ICZM yet that work to date has insufficiently crossed disciplinary boundaries. Professor Visser has sought to fill that gap by bringing together a range of authors of wide geographical and disciplinary backgrounds who have consciously tried to challenge disciplinary limitations in their contributions to ICZM in theory and practice. First publication in the "http://www.aup.nl/mare">MARE Publication Series